Positive Solutions for a Class of Discrete Mixed Boundary Value Problems with the p,q-Laplacian Operator - Cuiping Li; Zhan Zhou (Discrete Dynamics in Nature and Society)
In this paper, we consider the existence of solutions for the discrete mixed boundary value problems involving p,q-Laplacian operator. By using critical points theory, we obtain the existence of at least two positive solutions for the boundary value problem under appropriate assumptions on the nonlinearity.